Binder Jetting 3D Printing of Biomass–Fungi Composite Materials: A Preliminary Experimental Study - Yeasir Mohammad Akib; Caleb Oliver Bedsole; Jackson Sanders; Harlie Warren; Zhijian Pei; Brian D. Shaw (Biomimetics)
This paper reports on a preliminary experimental study on binder jetting 3D printing of biomass–fungi composite materials. Biomass–fungi composite materials have potential applications in the packaging, furniture, and construction industries. Biomass particles (prepared from agricultural residues) act as the substrate of the composite materials. The filamentous roots of fungi intertwine and bind biomass particles together. In this study, the biomass (hemp hurd) powders used had two distinct average particle sizes. The liquid binder used contained fungi (Trametes versicolor) cells. T-shaped samples were printed using a lab-designed binder jetting setup. Printed samples were kept inside an incubator oven for four days to allow fungi to grow. Afterward, loose biomass powder was removed from the T-shaped samples. The samples were then kept inside the incubator oven for eight more days to allow further fungal growth. The samples were subsequently placed in an oven at 120 °C for four hours to terminate all fungal activity in the samples. SEM micrographs were taken of the cross-sectional surfaces of the samples. The micrographs showed a significant presence of fungi hyphae inside the printed samples, providing evidence of the binding of biomass particles by the hyphae.